Peran Street-Level Bureaucrats dalam Advokasi Kebijakan: Garda Terdepan Perubahan Sosial di Tingkat Lokal - Nugraha, Imam; Setiabudi, Adi; Dewi, Maya Puspita (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Street-level bureaucrats (SLBs) play a central role in the implementation and advocacy of public policies, particularly at the local community level. This study examines the role of bureaucratic actors at the field level such as RT Heads, RWs, Hamlet Heads, and Village Heads in bridging communication between the government and the community. Using a qualitative approach based on literature and case studies, the study analyzes how SLBs interpret, implement, and advocate for policies in the midst of resource constraints and bureaucratic challenges. The findings show that SLBs play a role not only as policy implementers, but also agents of change with innovation and advocacy from below. However, limited training and work pressure are the main obstacles. This study recommends capacity building and systemic support for SLBs to make policy advocacy more effective and sustainable.